2007
DOI: 10.1016/j.jfca.2006.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of polyphenolic extract of monofloral honeybee-collected pollen from mesquite (Prosopis juliflora, Leguminosae)

Abstract: The antioxidant capacity related to the phenolic composition of monospecific honeybee-collected pollen extract from the mesquite tree (Prosopis juliflora) from Durango, Mexico, was evaluated in an in vitro-biological system (as inhibitor of lipid peroxidation on mouse hepatic microsomal preparations) and in an in vivo system (on homogenized liver of bromobenzene-intoxicated mice) by quantification of thiobarbituric acid-reactive substances (TBARS). The comparison of results obtained from these two different sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 19 publications
4
100
0
4
Order By: Relevance
“…Pollen is considered as an important source of flavonol glycosides and phenolic acids (Almaraz-Abarca et al, 2007;Wiermann & Vieth, 1983). Both classes of compounds, providing significant antioxidant properties (Campos, Da Cunha, Navarro, & Utrilla, 1994), vary in composition among different groups of plants with a species-specific tendency (AlmarazAbarca et al, 2004(AlmarazAbarca et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Pollen is considered as an important source of flavonol glycosides and phenolic acids (Almaraz-Abarca et al, 2007;Wiermann & Vieth, 1983). Both classes of compounds, providing significant antioxidant properties (Campos, Da Cunha, Navarro, & Utrilla, 1994), vary in composition among different groups of plants with a species-specific tendency (AlmarazAbarca et al, 2004(AlmarazAbarca et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of phenolic compounds depends on the chemical structure and can be determined by the action of the molecule as reducing agents (speed of free radical inactivation, reactivity with other antioxidants and metal chelating potential). In vitro trials have demonstrated that some flavonoids have greater antioxidant activity than vitamins E and C [12]. Epidemiologic studies have also demonstrated positive correlation between the increase in phenolic compound consumption with antioxidant action [13] and reduction of the risk of cardiovascular diseases and certain types of cancer [14].…”
mentioning
confidence: 99%
“…PF is known to have some components such as lectin, L-arabinose, 5-hydroxyl, quercetin (flavonoid), tryptamine (alkaloid) and apigenin [14]. Antioxidant activity of flavonoids present in PF has been reported [15]. The obtained results from the antioxidant capacity of honeybee-collected pollen extract from Prosopis juliflora suggested that it is an important source of flavonoids which can be considered as natural antioxidants [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant activity of flavonoids present in PF has been reported [15]. The obtained results from the antioxidant capacity of honeybee-collected pollen extract from Prosopis juliflora suggested that it is an important source of flavonoids which can be considered as natural antioxidants [15,16]. Alharbi et al [17] showed that flavonoids in PF act as strong antioxidant and decrease total cholesterol, triglycerides, malondialdehyde and also increase HDL-C in tetrachloride-induced hepatotoxicity rats.…”
Section: Introductionmentioning
confidence: 99%